Doubling Up or Moving Out? The Effect of International Labour Migration on Household Size - Kseniia Gatskova; Vladimir Kozlov (International Migration, 2019)
We use household panel data from Tajikistan to explore the change in living arrangements as a response to income shifts related to international labour migration. In addition, we analyse the interaction between the effect of idiosyncratic income increase resulting from a completed migration episode, and the effect of an aggregate shock – the global financial crisis – and show how different households adjust their household size during times of financial hardship. The empirical evidence indicates that while current migration is associated with an increase in household size, a completed migration episode two years before the interview was followed by family members moving out. At the same time, our empirical analysis demonstrates that migrant families doubled up in response to a financial crisis to the same extent as non-migrant families, which suggests that labour migration in Tajikistan does not insure against economic shocks in the long run.
Additional information: This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions.
Keywords: 330; labour migration; living conditions; Tajikistan